Cesium-137 in an alpine watershed - Hubbard, John Edward, author; Striffler, William D. (William David), advisor; Whicker, F. Ward, committee member; Goodell, B. C., committee member; Schmehl, W. R., committee member (Colorado State University. Libraries, 1968)
A study was made of the distribution of the fallout radionuclide Cs-137 on the surface and in the stream channel of an alpine watershed in the Colorado Front Range. Cs-137 activities of the surface (mean = 266 nCi/m2) were considerably higher than at Fort Collins, Colorado. The effects of snow-accumulation, soil-vegetation complexes and the hydrologic surface were studied in relation to Cs-137 activity. Snow accumulation areas contained significantly more Cs-137 than snow-free areas. Alpine Bog contained significantly more Cs-137 than did Alpine Turf and Alpine Meadow soils. Micro-channels and micro-depressions had significantly higher levels of Cs-137 activity than areas characterized as surface runoff. Concentrations of Cs-137 in stream bottom sediments and stream vegetation decrease exponentially downstream with distance from a permanent snowfield at the headwaters. There is some evidence that Cs-137 in sediments is accumulating in a marshy area where the stream flows across the moraine of a former mountain glacier. Cs-137 activities of the sediments were not highly related to percent silt+clay. Evidence did not support the hypothesis that most Cs-137 would concentrate in the silt+clay as it moved downstream. Significant quantities of Cs-137 were not found in stream water or the 1967 or 1968 snowpack. Measurable Cs-137 activities were found in litter and inorganic materials in and about the permanent snowfield, and in moss on rocks in the stream channel.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Radioactive fallout; Watersheds